2022
DOI: 10.3310/ijfm4802
|View full text |Cite
|
Sign up to set email alerts
|

EarlyCDT Lung blood test for risk classification of solid pulmonary nodules: systematic review and economic evaluation

Abstract: Background EarlyCDT Lung (Oncimmune Holdings plc, Nottingham, UK) is a blood test to assess malignancy risk in people with solid pulmonary nodules. It measures the presence of seven lung cancer-associated autoantibodies. Elevated levels of these autoantibodies may indicate malignant disease. The results of the test might be used to modify the risk of malignancy estimated by existing risk calculators, including the Brock and Herder models. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 217 publications
0
4
0
Order By: Relevance
“…Therefore, the existing evidence alludes to the insufficient sensitivity of the EarlyCDT ® Lung test to be used as part of the inclusion criteria in the LDCT LCS program [ 21 ]. Similarly, there is low sensitivity in risk stratification of patients with solid pulmonary nodules [ 22 ]. On these grounds, this test does not meet any of the LCS biomarker requirements that would make it a useful tool complementing LCS programs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the existing evidence alludes to the insufficient sensitivity of the EarlyCDT ® Lung test to be used as part of the inclusion criteria in the LDCT LCS program [ 21 ]. Similarly, there is low sensitivity in risk stratification of patients with solid pulmonary nodules [ 22 ]. On these grounds, this test does not meet any of the LCS biomarker requirements that would make it a useful tool complementing LCS programs.…”
Section: Resultsmentioning
confidence: 99%
“…An audit study on the clinical utility of EarlyCDT lung also demonstrated a 41% sensitivity with 57% of the detected cancers found in early stage (I/II) ( 13 ). However, a recent systematic review of studies utilizing EarlyCDT lung alone in five different cohorts revealed a decreased sensitivity of 22% at 92% specificity, compared to the estimate by the manufacturer ( 14 ). This result demonstrates the limitations of EarlyCDT lung as a stand-alone tool.…”
Section: Plasma Markersmentioning
confidence: 98%
“…. 22 , 23 The ECLS trial was a phase 4 (screening) biomarker evaluation that addressed the question: 'Does using the EarlyCDT-Lung Test to identify those at high risk of lung cancer and any subsequent…”
Section: Introductionmentioning
confidence: 99%
“…. 22 , 23 The ECLS trial was a phase 4 (screening) biomarker evaluation that addressed the question:…”
Section: Introductionmentioning
confidence: 99%